CREATIVE TOURISM – ATTRACTING TOURISTS THROUGH ART AND INNOVATIONS - Anvarova Muhsinakhon Otabek kizi (TADQIQOTLAR, 2025)
Annotation: This article explores the concept of creative tourism as a modern approach to attracting visitors through art, culture, and innovative practices. Unlike traditional forms of tourism that primarily focus on passive sightseeing, creative tourism emphasizes active participation, cultural exchange, and experiential learning. By engaging tourists in creative activities such as workshops, artistic performances, and innovative cultural projects, destinations can strengthen their attractiveness, diversify tourism products, and support sustainable development. The study also highlights the role of creativity and innovation in enhancing cultural identity, promoting local heritage, and contributing to economic growth in the tourism sector.